Strategi dan Diplomasi Perang Rasulullah - Akhmad Saufan (Jurnal Lektur Keagamaan, 2015)
War is part of the phase of Prophet’s dakwah (proselytization). The war can’t be totally avoided by the Prophet; although he tried severely to stay off bloodshed. The enemy kept bullying, intimidating and browbeating whichforced the Prophet to make a war. War is among efforts done by the Prophet to maintain the continuity of Islam. The prophet PBUH involved directly in battle for twenty seven times. To win the war, strategies and tactics are important. This paper examines some strategies and politics of war during the prophet period. In addition to war, the Prophet used diplomacy and negotiation’s way in his dakwah. For example, the Prophet sent letters to the kings and rulers of neighboring countries to promote Islam. He also sent delegations to neighboring countries, such as Yemen, Palestine and Jordan. From historical notes, it was known that all wars done by the Prophet were based on the followers obedience of God and to defend the religion as obligated by Islamic law.